Активность вулкана Ключевской в ноябре 2019 – июне 2020 гг. - Черкашин Р.И.; Иванов В.В.; Озеров А.Ю.; Мельников Д.В.; Демянчук Ю.В. (My University, 2020)
Активность вулкана Ключевской в ноябре 2019 – июне 2020 гг.
Keywords: 38.37.25 Вулканология; Ключевской